Quality of Life among Primary Caregivers of Children with Cerebral Palsy Living in Sarlahi and Rautahat Districts of Nepal - Pandit, Bina; Singh, Jitendra Kumar; Karn, Ananda Kumar; Pandit, Rina (Journal of Nepal Health Research Council, 2021)
Background: The objective of this study was to determine the quality of life and factors associated with quality of life among primary caregivers of children with Cerebral palsy. Methods: A cross-sectional study was carried between primary caregivers of children with cerebral palsy in rehabilitation group and non-rehabilitation group. Purposive sampling technique was used to collect data Results: Median age of caregivers was 34 years (age 20-70 years), and there was significant difference between age in two groups (p=0.028). 83 (86.5%) caregivers were female with significant difference between gender in rehabilitation and non-rehabilitation group (p=0.03). Majority of primary caregivers were mother 71 (74%) in both groups. Among all 96 caregivers, 78.1% of caregivers had poor quality of life (Score in questionnaire below 75% taken as poor quality of life).There was no significant difference between quality of life in rehabilitation and non-rehabilitation group (p=0.42). Factors associated with quality of life in rehabilitation groups was illiteracy (p=0.005), aggressive nature of child (p=0.050), uncooperative nature of child (p=0.025), poor knowledge about child condition (p<0.001), and low financial support (p=0.051). Similarly, factor associated with quality of life in non-rehabilitation group was gross motor function classification system level of child (p< 0.001) and more perceived stress (p=0.048). Conclusions: Majority of primary caregivers was mother and had poor quality of life and there was no significant difference between overall quality of life of caregivers in rehabilitation and non-rehabilitation group. Keywords: Cerebral palsy; quality of life; primary caregivers